Рамочная классификация ископаемых энергетических и минеральных запасов и ресурсов Организации Объединенных Наций 2009 года, включая спецификации для ее применения - United Nations (United Nations, 2014)
This publication contains the text of the United Nations Framework Classification for Fossil Energy and Mineral Reserves and Resources 2009 (UNFC-2009) and the Specifications (basic rules) for its Application. UNFC-2009 is a universally acceptable and internationally applicable scheme for the classification and reporting of fossil energy and mineral reserves and resources and is currently the only classification in the world to do so. As with extractive activities, UNFC-2009 reflects conditions in the economic and social domain, including markets and government framework conditions, technological and industrial maturity and the ever present uncertainties. It provides a single framework on which to build international energy and mineral studies, analyze government resource management policies, plan industrial processes and allocate capital efficiently. The Specifications make UNFC-2009 operational. They set out the basic rules that are considered necessary to ensure an appropriate level of consistency in application. They provide additional instructions on how UNFC-2009 should be applied in specific circumstances. By covering all extractive activities, UNFC-2009 captures the common principles and provides a tool for consistent reporting for these activities, regardless of the commodity. It is a strong code that paves the way for improved global communications which will aid stability and security of supplies, governed by fewer and more widely understood rules and guidelines. The efficiencies to be gained through the global use of UNFC-2009 and its Specifications are substantial.